Stochastic Failure Analysis of Reinforced Thermoplastic Pipes Under Axial Loading and Internal Pressure - Wang, Yang-yang; Lou, Min; Wang, Yu; Wu, Wu-gang; Yang, Feng (China ocean engineering, 2022)
This study explores how parametric uncertainties in the production affect failure tensile loads of reinforced thermoplastic pipes (RTPs) under combined loading conditions. The stress distributions in RTPs are examined with three-dimensional (3D) elasticity theory, and the analytical micromechanics of composites are evaluated. To evaluate the failure mechanisms for RTPs, 3D Hashin—Yeh failure criteria are combined with the damage evolution model to establish a progressive failure model. The theoretical model has been validated through numerical simulations and axial tensile tests data. To analyze how randomness of relevant parameters affects the first-ply failure (FPF) tensile load and final failure (FF) tensile load in RTPs, many samples are produced with the Monte—Carlo approach. The stochastic analysis results are statistically evaluated through the Weibull probability density distribution function. For the randomness of production parameters, the failure tensile load of RTPs fluctuates near the mean value. As the ply number at the reinforced layer increases, the dispersion of failure tensile load increases, with a high probability that the FPF tensile load of RTPs is lower than the mean value.